Is cancer a good way to die? A population-based survey among older adults in the UK. (13th November 2015) - Vrinten, Charlotte; Wardle, Jane
Abstract: Background: Despite improved outcomes, cancer remains widely feared, often because of its association with death, a death that is seen as protracted and painful. Former Editor-in-chief of the BMJ, Richard Smith, therefore attracted much criticism when he suggested in a blog post that "cancer is the best way to die". But is his view such an idiosyncratic one? Methods: We conducted an online survey (Feb 5–9, 2015) in a UK population sample of people aged 50–70 years (n=391), with sampling quotas for sex and education. Five characteristics of a good death were selected from the end-of-life scientific literature: control over what happens when you die (for example, who is present or whether you die at home or in hospital), control over pain and other symptoms, time to settle affairs, time to say goodbye to loved ones, and living independently and with dignity until you die. Respondents were asked to rate the importance of each characteristic for their own death to ensure that they were applicable to a population sample. They also rated the likelihood of each characteristic for death from cancer and heart disease, the most common causes of adult mortality. In addition, we asked whether they agreed with Smith's view. The study was exempt from ethics approval. Findings: Our selection of characteristics of a good death was supported by at least 95% of respondents, indicating that these characteristics would be important for their own death (ranging from 371 respondents who thought it was important to have control over what happens when you die to 378 respondents who thought it was important to have control over pain and other symptoms). Death from cancer was rated as more likely to provide control over what happens (p<0·0001), control over pain and other symptoms (p=0·003), time to settle affairs (p=0·0003), and time to say goodbye to loved ones (p<0·0001) than death from heart disease, but there were no differences in living independently (p=0·23). 155 respondents (40%) agreed that cancer is "the best way to die", with no differences by age (p=0·29), sex (p=0·84), or education (p=0·07). Interpretation: Despite the media commotion, a surprisingly high proportion of older adults agreed with Smith that cancer is "the best way to die", and rated cancer as a better death than heart disease. One in two of us are likely to be diagnosed with cancer, so conversations about what constitutes a good death are important to help us all, and might in a small way help mitigate fear of cancer. Funding: This study was supported by a programme grant from Cancer Research UK awarded to JW (C1418/A14134). Both authors are funded by this grant. Cancer Research UK was not involved in the design of this study, collection, analysis, or interpretation of the results; in the writing of the abstract; or in the decision to submit for publication.